Variáveis que influenciam a escolha dos estudantes por cursos de pós-graduação Lato Sensu a distância na área de negócios - Eduardo Mendes Nascimento (2011)
Contemporary society places great value to knowledge, and, therefore, the higher education degree is considered very important. More recently there has been a significant increase in students interest for lato sensu specialized courses called managerial training courses, executive education, or Master Business Administration (MBA) justified by the highcompetition in the labor market. This context highly competitive and unstable results in a strong impact on the managers training and the pressure exerted by the companies is often known, because they want better results from their processes and business as well as rapidand reliable responses from their managers. Access to higher education degree is in some cases difficult for individuals who live far from major referral education centers, a fact evident in Brazil, a country with great territorial extension whose quality education is restricted just to some regions. For this reason, the Distance Learning (DL) has become animportant mode for effective democratization of graduation and post-graduation courses to students from any region of Brazil. Because of the resulting expectations from this context, it is necessary to analyze the quality of these courses in order to meet the interested peopleneeds and to satisfy their choices. With this in mind and from Scriven (1981) theory, this research overall objective was to identify and analyze the degree of importance attributed by Brazilian students to the variables that influence the choices for Distance Learning of lato sensu post-graduation in business area. For this purpose, sixteen variables have been raised that indicated being able to influence students and a developed questionnaire was administered to three hundred and fifty-four students from specialized courses in business at distance asking them to inform the degree of importance they attached to these variableson a scale ranging from 0 to 10. The respondents profile was 60% female, 47% married, 25% graduated in Business Administration, mean age of 36 years old, 75% working for the public sector, and 69% were in their first lato sensu specialization course at distance. Results showed that students rated flexibility, faculty, curriculum, and cost the mostimportant variables with mean scores equal to or greater than 9. Nine other variables, teaching methodologies, tutors, teaching materials, use of cutting-edge information and communication, institution financial sustainability, access to facilities, activities, contact with teachers and technical personnel administration, had a mean score from 8 to 8.9.Finally, the variables that had the lowest significance (scores below 7.9) were participation of colleagues, interaction among students, and equipment financing. The flexibility variable showed to be very important for students, which was evidenced in their comments about nodesire to face meetings.